Dead until dark - Harris, Charlaine (New York : Ace Books, 2008)
Sookie Stackhouse is a small town waitress who can read people's minds, which makes her keep to herself a lot. Then she meets Bill, and she can't hear a word he's thinking, but just when she thinks he's the man she's been waiting for her whole life she finds out he's a vampire and runs with a crowd suspected of murder.
Originally published: New York : Ace Books, 2001.
"Now the HBO original series Trueblood" -- cover.
Keywords: Stackhouse, Sookie (Fictitious character) -- Fiction; Waitresses -- Fiction; Telepathy -- Fiction; Vampires -- Fiction; Louisiana -- Fiction; Occult fiction; Horror tales; Humorous stories; Fantasy fiction; Mystery fiction